Shape optimization of a multi-element hydrofoil for hydrokinetic turbines using response surface methodology (2019)
This paper describes the optimization procedure of a two-dimensional multi-element hydrofoil shape during its design for small horizontal axis hydrokinetic turbines using response surface methodology. JavaFoil software was used for describing the hydrofoil performance under several combinations of geometrical parameters, such as the horizontal space (overlap), h, between the drag edge of the main element and the leading edge of the second element; the vertical distance (gap), d, of the flap from the main element trailing edge; and the flap deflection angle, . Different experimental designs aiming at the maximization of the lift-to-drag ratio were used. The maximal lift-to-drag ratio was found to be 69.9626 for , and equal to 2.0%, 18.4619% and 20°, respectively, being the factor exerting a considerable influence on the response variable. Key words. Hydrokinetic turbine, hydrofoil optimization, response surface methodology, design of experiments